Gas price caps and electricity production effects in the context of the Russo-Ukrainian War: modeling and new policy reforms - Werner Roeger; Paul J. J. Welfens (International Economics and Economic Policy, 2022)
The merit-order approach in the electricity market, which is in widespread use across the EU27 and the UK, has proven to be somewhat economically problematic in the context of the Russo-Ukrainian War. The massively increased gas prices since summer 2022—in the context of Russian supply cuts to the EU—has led to an abnormally high electricity price. Using the merit order approach, the price of electricity increases enormously if, as is often the case, gas is the last type of energy still realized in power generation; this leads to artificial increases in returns for all other types of energy providers whose output is used in power generation. Gas price increases by Russia or Russian supply cuts to the EU can increase the price of electricity and also the rate of inflation, as well as depress real income. The electricity price shock can be countered by switching—temporarily—to a modified regulation of the electricity market for a few years with a gas price subsidy in the electricity market. In a macroeconomic analysis, we identify both the output losses and adverse distributional effects of a gas price hike and find that a gas price subsidy is superior in stabilizing output and employment compared to a transfer; it also at least partially addresses certain distributional issues by reducing windfall profits in the electricity market. The study advocates a combination of gas price subsidies only in the electricity market and targeted transfers to households to meet both efficiency and distributional targets. The macro-analysis findings presented herein should be considered carefully, as they could minimize the welfare losses in the EU and the UK. As regards the expansion of renewable energy-based electricity, it is shown herein that the cost-differential between gas-fired power stations and renewable electricity is critical—large cost differentials imply barriers for the expansion of electricity generation from renewables unless there is a price regulation of electricity. There is the potential for an inefficient adjustment path due to nonlinearities. With a proposed narrow gas price cap for the electricity market only, the associated initial deficit related to necessary subsidies is, of course, much smaller than in the case of a general gas price cap.
Keywords: D58; L51; L52; Q41; E64; Q48; 330; Power sector; Russo-Ukrainian War; Gas prices; Macro modeling; Subsidy policy; Transfers; DSGE model